It s flexible and versatile - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Rubber By M A Delabarre & J B Serier, Tropical Agriculuralist, Macmillan-CTA, 2000. 154 pp. ISBN 0 333 68355 2 CTA number 1011. 10 credit points